Stage IV breast cancer: a population‐based study about prognostic factors according to HER2 and HR status. (10th March 2015) - Bertaut, A.; Mounier, M.; Desmoulins, I.; Guiu, S.; Beltjens, F.; Darut‐Jouve, A.; Ponnelle, T.; Arnould, L.; Arveux, P.
<x xml:space="preserve">Abstract</x> We aim to describe trends in net survival (NS) and to assess the prognostic factors among women with de novo metastatic breast cancer (MBC) according to human epidermal growth factor receptor 2 (HER2) and hormone receptor (HR) status. Data on women suffering from de novo MBC and diagnosed from 1998 to 2009 were provided by the Côte‐d'Or breast cancer registry. NS was described using the Pohar Perme estimator and prognostic factors were investigated in a generalised linear model. We identified 232 patients (mean age = 64.7). Median NS was 29.2 months, 1‐ and 5‐year NS were 76% and 26% respectively. The survival trend in patients with HER2‐positive tumours who did not receive trastuzumab was similar to that in women with triple‐negative tumours. A higher relative excess risk of death by cancer was observed for high‐grade tumours [RER, relative excess rates = 1.76 (95% CI, confidence intervals: 1.17–2.62) for Scarff Bloom Richardson grade 3 vs. 1 + 2], while a lower risk was observed for luminal tumours [RER = 0.49 (95% CI: 0.27–0.89)] and HER2‐positive tumours treated with trastuzumab [RER = 0.28 (95% CI: 0.14–0.59)], both compared with triple‐negative tumours. Surgery of the primary tumour was associated with better survival [RER = 0.43 (95% CI: 0.28–0.68)]. With half of the women dead before 29 months, stage IV breast cancer still has a bleak outlook. Progress should continue with new target therapies for both HR and HER2 receptors.